Wages and jobs in the Portuguese air transport industry - Barbot,Cristina (2013)
Using a large matched employer-employee data set with information at both the worker and the company level we characterise the Portuguese airlines' employment structure and, by comparing it with the general structure of the Portuguese labour force, we stress the particularities of the sector. Based on the Heckman selection model, we develop an analysis of the variables that influence wages in this sector and which contribute to its differentiation from the general labour market. Particular attention is paid to the disparity among different types of jobs in the air transportation sector, namely amongst flight crews and land personnel. We also analyse the differences between regular and non-regular sub-sectors. Our main findings indicate that the aviation sector labour force is clearly specific regarding gender distribution and human capital accumulated by its workers. Moreover, some professions, pilots in particular, have important specificities compared to other jobs even within the sector. We also find that wages are strongly influenced by levels of education, tenure and experience as well as professional categories, which appears as an important specificity of this sector.